Chronic E-Cigarette Aerosol Inhalation Alters the Immune State of the Lungs and Increases ACE2 Expression, Raising Concern for Altered Response and Susceptibility to SARS-CoV-2 - Masso-Silva, Jorge A.; Moshensky, Alexander; Shin, John; Olay, Jarod; Nilaad, Sedtavut; Advani, Ira; Bojanowski, Christine M.; Crotty, Shane; Li, Wei Tse; Ongkeko, Weg M.; Singla, Sunit; Crotty Alexander, Laura E. (Frontiers in Physiology, 2021)
Conventional smoking is known to both increase susceptibility to infection and drive inflammation within the lungs. Recently, smokers have been found to be at higher risk of developing severe forms of COVID-19. E-cigarette aerosol inhalation (vaping) has been associated with several inflammatory lung disorders, including the recent e-cigarette or vaping product use-associated lung injury (EVALI) epidemic, but has not yet been proven to alter host susceptibility to pathogens such as SARS-CoV-2. To assess the impact of vaping on lung inflammatory pathways, including the ACE2 receptor known to be involved in SARS-CoV-2 infection, mice were exposed to e-cigarette aerosols for 60 minutes daily for 1-6 months and underwent gene expression analysis. Hierarchical clustering revealed extensive gene expression changes occurred in the lungs of both inbred C57BL/6 mice and outbred CD1 mice, with 2,933 gene expression changes in C57BL/6 mice, and 2,818 gene expression changes in CD1 mice (> abs 1.25-fold change). Particularly large reductions in Igj and CD4 were identified, indicating impairment of host responses to pathogens via reductions in IgA and CD4 T-cells. CD177, facmr, tlr9, fcgr1, and ccr2 were also reduced, consistent with diminished host defenses via decreased neutrophils and/or monocytes in the lungs. Gene set enrichment (GSE) plots demonstrated upregulation of gene expression related to cell activation specifically in neutrophils. As neutrophils are a potential driver of acute lung injury in COVID-19, increased neutrophil activation in the lungs suggests that vapers are at higher risk of developing more severe forms of COVID-19. The receptor through which SARS-CoV-2 infects host cells, ACE2, was found to be upregulated 33% in mice exposed to e-cigarette aerosols generated from Vape pens, and up 3-fold in mice exposed to JUUL Mint aerosols, suggesting an increased susceptibility to this novel coronavirus infection both with unflavored, nicotine containing vaping aerosols and with mint flavoring. These data demonstrate that chronic, daily inhalation of e-cigarette aerosols fundamentally alters the inflammatory and immune state of the lungs. Thus, e-cigarette vapers may be at higher risk of developing infections and inflammatory disorders of the lungs.